HISTORISITAS TRADISI TA’WIL AL-QUR’AN AHL AS-SUNNAH: Kajian Sejarah Ta’wil dengan Kerangka Analisis History of Ideas - Syamsul Wathani (Al Irfani: Journal of Al Qur'anic and Tafsir, 2020)
“The tradition of Ta’wil al-Qur’an has not developed as rapidly as the tradition of interpretation. It could be that this is because the study of the ta'wil of the Quran has received less attention, even though the history of the representation of the Quran is very developed. This article Discuss the history of the ta’wil al-Qur’an in the Ahl as-Sunnah Theology tradition. The study framework used is the history of thoughts/ideas. Within the framework of this study, this article finds several conclusions: As an exegetical method, classical Islamic discourse has developed many ta'wil as a means of interpretation and theory in understanding the text of the Qur'an. The Historical Discussion of thinking about the ta’wil of the Qur'an in the tradition of ahl as-Sunnah shows the development of the diversity of thoughts and knowledge used in interpreting the al-Qur'an. Ibn Qutaybah in Ta'wil Musykil Al-Qur'an uses linguistic analysis, gives birth to linguistic takwil (at-ta'wil al-lughawi), al-Ghazali wrote Qanun at Ta’wil which depicts the work of the Qur'anic representations with a ta'wil Theological, al-Razi wrote Mafatih al-Ghaib with a style of thought ta'wil falsafi, Ibn' Arabi wrote al-Futuhat al-Makkiyyah with a Sufistic interpretation / ta'wil, and asy-Syatibi wrote al-Muwafaqat offering a paradigm of Ta 'wil Ushuli.”